2022
DOI: 10.1021/acsami.2c11265
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Electric-Field-Independent Mobilities in Thick-Film Organic Solar Cells

Abstract: In organic solar cells (OSCs), a thick active layer usually yields a higher photocurrent with broader optical absorption than a thin active layer. In fact, a ∼300 nm thick active layer is more compatible with large-area processing methods and theoretically should be a better spot for efficiency optimization. However, the bottleneck of developing high-efficiency thick-film OSCs is the loss in fill factor (FF). The origin of the FF loss is not clearly understood, and there a direct method to identify photoactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…PTQ10 and PM7, on the other hand, slightly underperform for very thin films compared to the other donors; however, PTQ10 displays a remarkable steadiness in performance for thicker layers, and thus provides a wider processing window, which is well in accordance with different studies, where low thickness dependencies for the FF are observed in combination with PTQ10. [56,[61][62][63][64] This underlines its suitability for upscaling-PTQ10 is able to form a high-performing device within a broad thickness range and is a cost-effective material-and was thus selected as active donor material of choice for fully solution-processed, semitransparent devices.…”
Section: Photoactive Layer: Balancing Layer Thickness and Performancementioning
confidence: 99%
“…PTQ10 and PM7, on the other hand, slightly underperform for very thin films compared to the other donors; however, PTQ10 displays a remarkable steadiness in performance for thicker layers, and thus provides a wider processing window, which is well in accordance with different studies, where low thickness dependencies for the FF are observed in combination with PTQ10. [56,[61][62][63][64] This underlines its suitability for upscaling-PTQ10 is able to form a high-performing device within a broad thickness range and is a cost-effective material-and was thus selected as active donor material of choice for fully solution-processed, semitransparent devices.…”
Section: Photoactive Layer: Balancing Layer Thickness and Performancementioning
confidence: 99%
“…Consequently, it is the low carrier mobility that limits the performance of thick active‐layer OSCs, resulting in the reduction of the FF that is mainly determined by the competition between the charge recombination and charge extraction. [ 18,46‐47 ]…”
Section: Mechanism For Efficiency Lossmentioning
confidence: 99%
“…(c) Key photovoltaic parameters of PM6:N3:PC 71 BM and PTQ10:N3:PC 71 BM OSC devices at different active layer thicknesses. Reproduced with permission, [ 18 ] Copyright 2022, American Chemical Society.…”
Section: Mechanism For Efficiency Lossmentioning
confidence: 99%
See 2 more Smart Citations